2009
DOI: 10.1021/jp809700f
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Cysteine Dioxygenase Enzymes Contain a 3-His Ligand Motif Rather than a 2His/1Asp Motif Like Most Nonheme Dioxygenases?

Abstract: Density functional theory calculations on the oxygen activation process in cysteine dioxygenase (CDO) and three active site mutants whereby one histidine group is replaced by a carboxylic acid group are reported. The calculations predict an oxygen activation mechanism that starts from an Fe(III)-O-O(*) complex that has close lying singlet, triplet, and quintet spin states. A subsequent spin state crossing to the quintet spin state surfaces leads to formation of a ring-structure whereby an O-S bond is formed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 94 publications
4
72
0
Order By: Relevance
“…20; 22 Spectroscopic studies show Cys binds to the enzyme first and creates the oxygen binding site, 23; 24; 25 but except for the recent evidence for a fleeting UV-absorbing oxygen-bound intermediate, 26 spectroscopic evidence for discrete intermediates has been unobtainable, 23; 24; 25; 27 and the mechanism of CDO remains uncertain (e.g. 2829 and 30; 31; 32; 33 and 25; 30 ). A high resolution crystal structure of a Cys-persulfenate/persulfenic acid complex with wild-type mammalian CDO revealed geometries for how Cys and O 2 may coordinate the iron and a central role for Tyr157-OH (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20; 22 Spectroscopic studies show Cys binds to the enzyme first and creates the oxygen binding site, 23; 24; 25 but except for the recent evidence for a fleeting UV-absorbing oxygen-bound intermediate, 26 spectroscopic evidence for discrete intermediates has been unobtainable, 23; 24; 25; 27 and the mechanism of CDO remains uncertain (e.g. 2829 and 30; 31; 32; 33 and 25; 30 ). A high resolution crystal structure of a Cys-persulfenate/persulfenic acid complex with wild-type mammalian CDO revealed geometries for how Cys and O 2 may coordinate the iron and a central role for Tyr157-OH (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…28 We proposed that the changes were due to deprotonation of Tyr157, as it is located close to both oxygen atoms of the persulfenate where it could influence oxygen binding. As the persulfenate formed in the crystal is not turned over to make CSA, 29 and calculations indicate other pathways are of lower energy, 31; 32; 33; 34 the persulfenate/persulfenic acid may be an off-pathway complex rather than a true intermediate of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to nitrosyl complexes of other enzymes, CDO-Cys-NO has been found to be a low spin (LS) S = 1/2 complex with an electronic structure description of LS Fe II (S = 0) with NO• (S = 1/2), which has been invoked in reaction coordinate calculations. 26,39 …”
Section: Introductionmentioning
confidence: 99%
“…[106][107][108] Subsequent DFT studies gave further understanding of its mechanism and the oxygen activation process. 109,110 CDO is an important enzyme in mammalian physiology that regulates the cysteine concentration in the body. Thus, cysteine is a non-essential amino acid that is synthesized in the body from methionine.…”
Section: Cysteine Dioxygenase (Cdo)mentioning
confidence: 99%
“…H86D, H88D and H140D mutants. 110 These studies showed that the 3-His ligand motif in CDO is essential for optimal dioxygenation of the substrate. Thus, a carboxylic acid group located trans to the sulfur atom of cysteinate weakens the Fe-S bond and thereby leads to loss of this bond after the first oxygen transfer process.…”
Section: Cysteine Dioxygenase (Cdo)mentioning
confidence: 99%